A New Seismic Phase to Detect Mid‐Mantle Scatterers. Issue 2 (25th January 2023) - Yuan, Y.; Sun, D.; Thomas, C.
Abstract: Small‐scale mid‐mantle heterogeneities (<100 km) are revealed by various short‐period seismic waves with different sampling paths. Here, using dense stations in China, we present the observations of a new seismic phase that arrives as a PP precursor. This arrival represents a P‐wave scattered at mid‐mantle heterogeneities as PdpP ("d" indicates the depth of heterogeneity) and appears in two forms: (a) a wave train with increasing slowness from P/Pdiff to PP slowness; (b) a single arrival with unique slowness between Pdiff and PP slowness. Waveform modeling results suggest that both types of PdpP signals can be simultaneously generated by lower mantle scatterers with scales larger than 20 km, situated close to the source region. Furthermore, focusing on the observations of PdpP from Fiji‐Tonga earthquakes, we locate a series of scatterers at depth of 800–1, 350 km that may be related to the Pacific slab subducting along the Tonga‐Kermadec trench. Plain Language Summary: Mid‐mantle heterogeneities with a scale of less than 100 km are important for better understanding the chemistry and evolution of the Earth's mantle. However, seismic imaging of these heterogeneities is limited by the distribution of earthquakes and stations required for the specified seismic phases used. In this study, we identify a new seismic phase, called PdpP, which is a P wave top‐side reflection from a mid‐mantle heterogeneity near the source at a depth of "d" and a second reflection at the surface. Then, we successfully simulate the PdpP phase with a model containing scatterers randomly distributed in mid‐ to lower mantle. The high sensitivity of PdpP phase to the locations and scales of the mid‐mantle scatterers suggests that this new phase is ideal for detecting the mid‐mantle heterogeneities. Finally, we focus on using this new phase to locate a series of lower mantle scatterers beneath the Fiji‐Tonga region and show these scatterers are related to the subducted Pacific slab. Key Points: We present observations of two types of "unknown" phase in PP precursor, which are identified as the PdpP from mid‐mantle scatterers "Unknown" phase can be simulated by a model containing scatterers randomly distributed in the mid‐mantle Subduction‐related mid‐mantle scatterers are located beneath the Fiji‐Tonga region with the PdpP phase